PECULIARITIES OF GROWTH AND DEVELOPMENT OF COMMON CHICORY PLANTS BEFORE AND AFTER WINTERING - Tkach , O. V. (Scientific Progress & Innovations, 2020)
In recent years, we have observed the tendencies in the regularities of climate change that require ap- propriate corrections in crop cultivation technological operations, common (large-rooted) chicory, in par- ticular. However, there are insufficient research data on the effect of cover crops, post-mowing and post- harvesting common chicory sown areas on seed productivity in the conditions of the Right-Bank Forest- Steppe of Ukraine. This is the relevance and practical significance of the corresponding investigation. Main research methods were field and laboratory. The studies were conducted in the experimental field of Khmel- nytskyi State Agricultural Research Station of the Institute of Feeds and Agriculture of Podillia of the NAASU during 2016–2018. The study results have shown that the highest field germination of common chic- ory seeds was under cover crops, namely under winter wheat cover – 37.2 %, which was 5.0 % higher than spring barley and 2.2 % higher than winter barley. It has been found that common chicory plants wintered by 82.4 % better after the post–mowing harvesting of vetch-oat mixture (for green feed), and also by 78.0 % after post–harvesting winter barley grain. The lowest wintering rate of chicory plants was obtained after crop under-sowing of winter wheat cover, only 51.0 %, which was 18 % less than under cover of spring bar- ley and 14.9 % less than under winter barley cover. High yield of common chicory seeds was obtained from under-sowing of spring barley cover – 0.415 t/ha. The yield turned out to be slightly lower in the variants of winter wheat and winter barley cover under-sowing – 0.351 and 0.294 t/ha, respectively. In case of cultivat- ing common chicory seeds by non-seedling method in post–mowing and post-harvesting plant areas, there was also a decrease in seed yield by 0.065 t/ha and 0.117 t/ha as compared with the variant of spring barley cover under-sowing. This was primarily connected both with moisture regime and temperature characteris- tics in May – August. The highest thousand-seed weight was in the variant of post–mowing cultivation – 1.39 g at seed yield of 0.350 t/ha, i.e., despite seed size, the yield was low. Such regularity testifies to thin- ning of crops because of insufficient moistening in the summer period, which was finally also reflected on seed productivity.